Axial compressive tests and resistance prediction of UHTCC-encased circular steel tubular columns - Chen, Yun-Long; Tong, Jing-Zhong; Li, Qing-Hua; Shen, Luming; Xu, Shi-Lang (Engineering structures, 2025)
Ultra-high toughness cementitious composite (UHTCC), characterized by its superior crack resistance and ultra-high ductility, exhibits great potential for application in advanced structural systems, especially subject to extreme environments such as highly corrosive regions. This research proposes a new type of UHTCC-encased circular steel tubular (UEST) column, which synergistically combines the high load-bearing efficiency of inner steel tubes with the superior durability of the outer UHTCC layer. Five experimental specimens were designed to examine the axial compression behavior of UEST columns with different shear connections, including studs and perfobond leiste (PBL) connectors. The experimental results indicate that UHTCC encasement significantly improves the axial resistance, ductility, and post-buckling performance of the structural system, with PBL connectors outperforming studs in delaying steel tube buckling and improving structural ductility. Based on the experimental and theoretical analyses, an axial resistance prediction model for UEST columns was developed, incorporating the effects of local buckling. The proposed model was validated against experimental results and finite element (FE) simulations, achieving an average prediction error of 2.7 %. Furthermore, a critical arc length-to-thickness ratio was proposed to provide practical design suggestions for optimizing UEST column configurations. •UHTCC can achieve high toughness and excellent cracking-resistant performance.•Axial compressive performance of UHTCC-encased steel tubular column is investigated.•A novel resistance prediction model is established for UEST columns.•Arc length-to-thickness ratio is proposed to describe local buckling behavior of UEST columns.